Tasarruf al-Imam Manutun bi al-Maslahah: Analisis Kebijakan Makan Bergizi Gratis Pada Era Pemerintahan Prabowo Subianto - Nur Alifah (Al-Istinbath : Jurnal Ilmu Hukum dan Hukum Keluarga Islam, 2026)
This article analyzes the Free Nutritious Meals (MBG) policy introduced during the administration of Prabowo Subianto through the lens of Islamic political jurisprudence (fiqh siyasah), particularly the principle of tasarruf al-imām ‘ala al-ra‘iyyah manūṭun bi al-maṣlaḥah (a ruler’s actions must be based on public welfare). The MBG program is a strategic initiative to address Indonesia's persistent issues of stunting and malnutrition, especially among students and impoverished communities. However, its implementation faces several challenges, particularly in the uneven distribution and focus on urban areas. This study employs a descriptive qualitative approach through literature review and normative-theological analysis. The findings indicate that MBG embodies the essence of maṣlaḥah and can be classified as a legitimate policy in Islamic governance, provided it is implemented justly, proportionally, and prioritizes marginalized groups. The study recommends comprehensive needs mapping, participatory policy evaluation, and integration of maqāṣid al-sharī‘ah values to ensure that MBG truly serves as an instrument of social justice and public welfare.